Introduction to biomolecular structure and biophysics : basics of biophysics - Misra, Gauri (Springer, 2017)
This comprehensive book presents a modern concept in biophysics based on recently published research. It highlights various aspects of the biophysical fundamentals and techniques that are currently used to study different physical properties of biomolecules, and relates the biological phenomenon with the underlying physical concepts. The content is divided into nine chapters summarizing the structural details of proteins, including recently discovered novel folds, higher order structures of nucleic acids, as well as lipids and the physical forces governing the macromolecular interactions which are essential for the various biological processes. It also provides insights into recent advances in biophysical techniques including Hydrogen Deuterium Exchange with Mass Spectrometry (HDX-MS), Small Angle X-ray Scattering (SAXS) and cryo Electron Microscopy (cryo EM), supplemented with interesting experimental data. It is a valuable reference resource for anyone with a desire to gain a better understanding of the fundamentals of biophysical concepts and techniques used to study important biomolecules.
Keywords: Biophysics.; elektronické knihy; electronic books